Age-Related, Regional, Hemispheric, and Medial-Lateral Differences in Myelin Integrity in Vivo in the Normal Adult Brain - Armstrong, Carol L.; Traipe, Elfrides; Hunter, Jill V.; Haselgrove, John C.; Ledakis, George E.; Tallent, Emily M.; Shera, David; van Buchem, Mark A. (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Clinical validation of magnetization transfer (MT) imaging is important for investigating clinical disease and organization of normal brain function. We determined whether an in vivo quantitative measure sensitive to white matter is distributed in functionally important ways.METHODS: Axial 1.5-T MR images with and those without MT were obtained. MT ratios (MTRs) were computed for 33 regions of interest (ROIs) in 27 healthy adults (aged 18–69 years) without evidence of cognitive or radiographic abnormalities. Three tests of reliability yielded coefficients above 0.97. MTRs for the whole brain, groups of structures, and individual ROIs were calculated. Low standard errors confirmed the consistency of the technique.RESULTS: Age, education, sex, and hand dominance were not correlated with whole-brain MTR (mean = 37.35, SD = 1.25), but age was associated with the cerebellum and some lobes at a trend level. MTRs were as follows, in descending order: corpus callosum, cingulate, white matter, brain stem, subcortical nuclei, and cerebellum. MTRs were selectively higher in the prefrontal lobe versus the posterior frontal lobe and in the lateral temporal lobe versus medial temporal lobe. MTR was higher in the left hemisphere than in the right hemisphere for the whole brain, frontal and temporal lobes, and lenticular nuclei.CONCLUSION: MT imaging showed selective age, medial-lateral, and hemispheric differences, giving evidence of normal aging effects on the white matter in the absence of T2- weighted hyperintensities. These differences support neurocognitive theories of the organization of brain function. MT imaging appears to be a robust technique for use in cognitive neuroscience.